Tourism Climate Index in Some Localities of Georgia and North Caucasus (Russia) - Amiranashvili, Avtandil G.; Japaridze, Nino D.; Kartvelishvili, Liana G.; Khazaradze, Ketevan R.; Matzarakis, Andreas; Povolotskaya, Nina P.; Senik, Irina A. (Journals of Georgian Geophysical Society, 2018)
Results of investigation of monthly values of the Tourism Climate Index (TCI) in some localities of Georgia (21 localities) and North Caucasus (Russia, 6 localities) are represented. Height of these localities varied from 3 to 2194 m above sea level. Correlation and regression analysis of the connection of mortality by cardiovascular deceases in Tbilisi with the values of TCI and its separate components is carried out. This analysis confirmed the representativeness of the use of the scale of TCI as bioclimatic indicator for the investigated region (as a whole, with an increase of values of TCI it is noted the decrease of mortality). The statistical characteristics of values of TCI are represented. In particular it is obtained that with an increase of the height of locality, as a whole occurs the passage of bimodal intra-annual distribution of TCI to the single-modal. The vertical distribution of values of TCI on the average in the year, in the warm and cold periods, and also in the central months of year is studied. The detailed information about the categories of TCI for all investigated localities is represented.